2015
DOI: 10.1016/j.erss.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Sociality and electricity in the United Kingdom: The influence of household dynamics on everyday consumption

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Six respondents mentioned that they self-censored some energy discussions, both inside or A this indicates that some stigma is attached to the topic of low carbon energy practices and discussing money and energy bills. Within the home, it is often associated with the perception of nagging, which could relate to the concepts of domestic sociality [54]. Outside the home it can be perceived as seeming smug or judgemental, for example: T careful about though and that is appea there is a fine line you walk between trying to promote something and being an evangelist…”
Section: Self-censorshipmentioning
confidence: 99%
“…Six respondents mentioned that they self-censored some energy discussions, both inside or A this indicates that some stigma is attached to the topic of low carbon energy practices and discussing money and energy bills. Within the home, it is often associated with the perception of nagging, which could relate to the concepts of domestic sociality [54]. Outside the home it can be perceived as seeming smug or judgemental, for example: T careful about though and that is appea there is a fine line you walk between trying to promote something and being an evangelist…”
Section: Self-censorshipmentioning
confidence: 99%
“…Rich ethnographic and descriptive research highlights the important role of social dynamics in household energy use (e.g., Bell et al, 2015;Permana, Aziz, & Siong, 2015;Sardinou, 2007;Wilhite, Nakagami, & Murakoshi, 1996;Wilhite, Nakagami, Masuda, Yamaga, & Haneda, 1996). For example, Kleinschafer et al (2014) found that household members who act as "efficiency champions" can have a significant impact on household norms.…”
Section: Introductionmentioning
confidence: 99%
“…Abrahamse (2005) contrasts these intrapersonal "micro-level" factors with "macro-level" factors such as demographics, technologies, and culture. Interpersonal dynamics among household members are a middle or meso level of influence (between micro-and macro-per Abrahamse; Bell et al, 2015), less acknowledged in energy intervention research. However, conceptualizations of energy behaviors as social practices (Shove & Walker, 2014) or "energy cultures" (Stephenson et al, 2015), embedded in complex social and material contexts, are a ready foundation for more interdisciplinary social science approaches to energy interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Poznaka et al [48] analysed how and why the installation of smart metres changed households' electricity use. Frederiks et al [49] stress the importance of psychology and behavioural economics aspects and Bell et al [50] point out that households should be studied individually, that their practices result, among others, from social relations. Since agent based modelling is a technique that is used in these disciplines as well, it would be interesting technique in realising interdisciplinary research in this field.…”
Section: Model Limitationsmentioning
confidence: 99%